GE_GERICHTE P/21097/2015 vom 7. Dezember 2023 - GE Cour de justice (2023)
CLASSEMENT DE LA PROCÉDURE;FOR DE LA POURSUITE;ABUS DE CONFIANCE;GESTION DÉLOYALE;GÉRANT(SENS GÉNÉRAL) | CP.3; CP.8; CP.138; CP.158